The plan for a new Argentine capital: Technical and political transitions in the 1980s - Menazzi Canese, María Luján (2025)
The article analyses the project to move the Argentinian capital from Buenos Aires to Viedma, a small city located in the south, in 1986. The project enlightens the period as a juncture of both technical and political transitions. In technical terms, the proposal had a hybrid nature, articulating developmentalist planning perspectives with innovative objectives for the time. In political terms, the proposal reflected the contradictions of the period, in which re-foundational illusions and severe economic and political limitations were articulated. Crossing the technical and political dimensions, the initiative is suggestive of the role given to technicians within the democratic transition.